Contributos do currículo em prol de uma educação para a paz - Lima, Maria José Marques (2022)
The research “Contributions of the curriculum in favor of education for the peace” was submitted to the Institute of Education of the University of Minho, in order to obtain the degree of Doctor in Educational Sciences, in the specialty Curriculum Development. The general objective for the investigation was to understand the contributions of the curriculum in favor of an education for peace in a public school that serves young people and adults. It was developed through a descriptive qualitative research, through a case study of one of the schools called Centro de Educação de Jovens e Adultos (CEJA), in the city of Fortaleza/Ceará, Brazil. For data collection, we used document analysis, field records, participant observation and individual interviews (6 teachers, 1 coordinator, 1 employee and 3 students). It was based on the epistemological framework related to the concept of curriculum and its theories, the curriculum in Brazil and its legislation and the historical legacy of education for peace, making a relationship with the concept of curriculum and praxis, involving themes of relevance to the humanity, as people who inhabit the same planet. The analyzes show that CEJA is a school of opportunities, inclusive when it serves students from the age of 15 for elementary school and from the age of 18 for high school, offers enrollment throughout the school year, individualized student service, personalized. There are only nine CEJAs in the city of Fortaleza, a number considered small for its territorial size, as the public power needs to guarantee the right to study for everyone. As for curriculum development, there are actions and projects that are part of the school and, in a way, lead to a practical curriculum that provides meaningful learning, which contributes to education for peace, as actions and projects are proposed. to a knowledge that can emancipate the student in an active, participatory and critical vision. A curriculum guided by the premises of education for peace, within the scope of schools of the CEJA typology, is considered essential for the promotion of the well-being and success of subjects in the school environment and subsequent improvement of the capacitated integration of subjects in social and social contexts. cultural. Thus, the centrality of the curriculum in these school centers must be sought in an inter and transdisciplinary way, using the transversal themes of the National Curricular Common Base, as well as themes from official world documents. The research, in view of the results presented, is considered as a contribution to the academic community and, also, to public policies for the education of young people and adults, as well as the improvement of teaching activity